Parental Acceptance of Children with Cerebral Palsy among Muslim Families: A Qualitative Study on Indicators, Influencing Factors, and Challenges within a Family Counseling Framework - N Nurhastuti; Afdal Afdal; Miftahul Fikri; Syari Yuliana (Universitas Negeri Padang, 2026)
Parental acceptance is crucial for the development and well-being of children with cerebral palsy, yet it remains insufficiently studied within Muslim family settings. This research aims to examine the types of acceptance, the factors influencing them, and the challenges faced by Muslim parents of children with cerebral palsy in Padang, Indonesia, through the lens of family counselling. A qualitative case study approach was adopted, involving five parents of children with cerebral palsy at the Gadang Cerebral Palsy Foundation. Data collection involved in-depth face-to-face interviews and documentation, followed by thematic analysis. Findings showed that all five parents exhibited five main aspects of acceptance: (1) understanding children’s feelings, (2) recognising children’s rights, (3) understanding children’s expressions and desires, (4) respecting children’s differences, and (5) fulfilling children’s needs. Acceptance was mainly influenced by knowledge, personal experience, family support, and socioeconomic status, whereas hope and career considerations had less effect. Nonetheless, parents encountered significant challenges, such as parenting stress, limited social support, and difficulties in understanding their children’s physical, psychological, emotional, and communicative traits. These insights underscore the urgent necessity for structured family counselling programmes addressing parental stress and enhancing acceptance capacity among Muslim families caring for children with cerebral palsy.